Prophylaxis Pharmacological Management for Patients with Intraoperative Floppy Iris Syndrome Risk Due to ?1-Adrenergic Receptor Antagonists Use - Brigitta Marcia Budihardja; Ade Ajeng Cempakadewi (Majalah Oftalmologi Indonesia, 2022)
Introduction: Intraoperative floppy iris syndrome (IFIS) remains a challenge that increases the risk of complications in patients undergoing cataract surgery who use ?1-adrenergic receptor antagonists. To date, no definite consensus on a preventive strategy for IFIS is available. The aim of this review is to assess various pharmacological managements to prevent IFIS in high-risk patients. Methods: This review was based on Preferred Reporting Items for Systematic Reviews and Meta- Analyses guidelines. A systematic search using PubMed, Science Direct, Cochrane Library, and WorldCat database was performed. Quality of each study was evaluated using Cochrane Risk of Bias 2.0 (RoB 2.0), Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I), or Newcastle- Ottawa Scale (NOS). Results: The search identified 1589 articles of which 7 met the eligibility criteria. Experimental and observational studies between 2010 and 2018 were included. Pharmacological managements included in this review are administered in varying routes. Phenylephrine, lidocaine, a combination of lidocaine and epinephrine are given intracamerally. Other pharmacological managements included are sub-tenon injection of lidocaine, topical atropine, a combination of topical atropine with intracameral epinephrine, combined irrigation solution of phenylephrine and ketorolac, and mydriatic cocktail- soaked wick sponges. Conclusion: Various pharmacological managements for IFIS prophylaxis have shown promising potential. However, studies that evaluate the efficacy of each agent and comparison between these strategies are still limited. Further research is needed to determine the best prophylaxis strategy to reduce the incidence of IFIS.